Taxonomy of leptogenys ants (Formicidae: Ponerinae) in Sabah - Mohd Afifi Ahmad Hamdan (2015)
This study focuses on the taxonomy of ant genus Leptogenys (Formicidae: Ponerinae) in Sabah, Malaysia, Borneo. Study compose of three objectives namely to revise the ant genus Leptogenys of Sabah followed by the study of their distribution and nesting record. Specimen observation conducted mainly through the institutional image type specimen and fresh specimen collection. Fresh specimen collection samplings involve active manual sampling. Throughout the study, there are 12 known species distinguished namely L. borneensis Wheeler, 1919, L. chalybaea (Emery, 1887), L. diminuta (Smith, 1857), L. distinguenda (Emery 1887) stat. nov., L. kitteli (Mayr, 1879), L. kraepelini Forel 1905, L. mutabilis (Smith, 1861), Leptogenys modiglianii Emery 1900, L. myops (Emery, 1887), Leptogenys nero Forel 1913 stat. nov., L. parvula Emery, 1900, L. peugueti André 1887 and six new species Leptogenys hispida sp. nov, Leptogenys oculatus sp. nov, Leptogenys parvaborneensis sp. nov, Leptogenys scabra sp. nov, Leptogenys seikii sp. nov and Leptogenys spicata sp. nov. While the study on the distribution shown most of Leptogenys species habitat found in primary than secondary forests such as Danum Valley, Tawau Hill Park, Sapulut, and Maliau Basin. The Urban landscape and Small Island recorded so far does not support the habitat of Leptogenys. Nest of this ant comprise of dead wood, soil, leaf litter and below the stone.